A mixed‐valence complex of cobalt based on 3‐methoxysalicylaldoxime. Issue 4 (15th April 2014) - Yao, Tiantian; Lu, Jing; Li, Dacheng; Dou, Jianmin
<x xml:space="preserve">Abstract</x> A new tetranuclear mixed‐valence cobalt complex, namely di‐μ2‐azido‐diazidodiethanolbisμ2‐2‐[(hydroxyimino)methyl]‐6‐methoxyphenolatobisμ3‐6‐methoxy‐2‐[(oxidoimino)methyl]phenolatodicobalt(II)dicobalt(III) ethanol disolvate, [CoII2CoIII2(C8H7NO3)2(C8H8NO3)2(N3)4(C2H5OH)2]·2C2H5OH, has been synthesized by the reaction of Co(OAc)2·4H2O (OAc is acetate) with 3‐methoxysalicylaldoxime (H2mosao) in an ethanol solution. In the complex, the four Co cations all display distorted octahedral coordination environments and they are bridged by two κ2, κ1, κ1;μ3‐mosao2− ligands, two κ2, κ2;μ2‐Hmosao− ligands and two μ2‐N3− anions to form a tetranuclear [Co4N4O4] cluster. Adjacent clusters are connected through weak C—H...N and C—H...O interactions, resulting in a two‐dimensional supramolecular network parallel to the ac plane. The magnetic properties of the complex have also been studied.